Surging dynamics of South Rimo Glacier, Eastern Karakoram. (10th November 2021) - Jiang, Zongli; Wu, Kunpeng; Liu, Shiyin; Wang, Xin; Zhang, Yong; Tahir, Adnan Ahmad; Long, Sichun
Abstract: Describing the dynamic characteristics of glacier surge events is a precursor to being able to understand their driving mechanisms. Here, a comprehensive suite of surface velocities and surface elevation changes for the surging South Rimo Glacier (SRG), situated in the East Karakoram region, are obtained by offset-tracking from Sentinal-1A and geodetic method from TerraSAR-X/TanDEM-X and Ice, Cloud, and land Elevation Satellite-2 Advanced Topographic Laser Altimeter System. The surge of SRG initiated in the summer of 2018, and the rapid and dramatic increase in surface velocities reached a peak (∼12 m d −1 ) in August 2019. By the summer of 2020, the surface velocity of SRG had returned to its pre-surge level. We interpret that the evolution of the latest SRG surge was probably triggered by changes in subglacial thermal conditions, and was ultimately accelerated by hydrological processes. Based on historical analysis, a surge return period of ∼25–30 years prevails at SRG. Spatiotemporal analyses of surface velocities and elevation changes such as these can provide useful information about surge mechanisms and their controls.